METHODOLOGICAL APPROACHES AND TECHNOLOGIES OF FORMING PROFESSIONAL ERUDITION OF FUTURE TEACHERS IN THE CONDITIONS OF PEDAGOGICAL PRACTICE - Jurayeva Gulshodaxon Ibrohimjonovna (Scholar Express Journal, 2025)
The article examines the influence of practical work in the school environment on the development of teachers' erudition. The study was conducted in order to identify how the active involvement of teachers in practical activities within the school contributes to their professional growth and knowledge expansion. The author analyzes various methods of working with teachers, such as seminars, master classes, training courses and pedagogical practice. Special attention is paid to how these forms of practical work contribute to the deepening of teachers' knowledge in the field of the subject, pedagogical techniques, as well as to improving their professional competence. The results of the study can be useful both for teachers seeking self-development and for the school administration when planning professional development programs for staff.
Keywords: practical work in schools; formation of teacher erudition